Carbon: Eutectic Syntheses of Graphitic Carbon with High Pyrazinic Nitrogen Content (Adv. Mater. 6/2016). Issue 6 (5th February 2016) - Fechler, Nina; Zussblatt, Niels P.; Rothe, Regina; Schlögl, Robert; Willinger, Marc‐Georg; Chmelka, Bradley F.; Antonietti, Markus
Abstract : Starting from a powder mixture of ketones/urea, gentle heating results in liquefaction below the melting point of the respective components. The back‐cover image shows a polarized optical microscopy image of a liquid‐crystalline eutectic mixture in the supercooled liquidus, as discussed on page 1287 by N. Fechler and co‐workers. This indicates the coupling of the monomers toward larger, preorganized assemblies. From this precursor system, "C2N" carbon is synthesized.